Factores psicosociales en adolescentes de educación secundaria: un análisis mediante la herramienta POSIT. Psychosocial factors in adolescents of secondary education: an analysis using the POSIT tool. - Jiménez Gutiérrez, María José; Gaona Sánchez, Luis David (My University, 2024)
Adolescence is a stage marked by psychosocial factors such as the search for autonomy, consolidation of identity, peer group pressure, and adaptation to the school environment, which influence emotional and social development. This study aimed to determine psychosocial factors in high school students of an educational unit in Arenillas, El Oro, using the POSIT questionnaire (α = 0.74), which assesses seven dimensions of adolescent well-being. A quantitative, descriptive, cross-sectional study was conducted with 280 students selected by non-probabilistic sampling. The results showed that 27.0% reported school difficulties associated with substance use and 20.3% expressed persistent cravings. In mental health, 67.6% reported feeling lonely and 66.5% reported concentration problems. At the family level, 42.3% reported conflicts between parents and 48.0% frequently argued with them. In addition, 34.5% had friends with violent behavior, 40.6% presented difficulties in organizing homework, and 69.0% felt undervalued by the school. It is concluded that comprehensive and culturally adapted interventions are required to strengthen mental health and prevent substance use in adolescents.
La adolescencia es una etapa marcada por factores psicosociales como la búsqueda de autonomía, consolidación de la identidad, presión del grupo de pares y adaptación al entorno escolar, los cuales influyen en el desarrollo emocional y social. Este estudio tuvo como objetivo determinar los factores psicosociales en estudiantes de bachillerato de una unidad educativa en Arenillas, El Oro, mediante el cuestionario POSIT (α = 0.74), que evalúa siete dimensiones del bienestar adolescente. Se realizó un estudio cuantitativo, descriptivo y transversal con 280 estudiantes seleccionados por muestreo no probabilístico. Los resultados mostraron que el 27.0% reportó dificultades escolares asociadas al consumo de sustancias y el 20.3% expresó deseos persistentes de consumir. En salud mental, el 67.6% manifestó sentirse solo y el 66.5% reportó problemas de concentración. A nivel familiar, el 42.3% indicó conflictos entre padres y el 48.0% discutía con ellos frecuentemente. Además, el 34.5% tenía amigos con conductas violentas, el 40.6% presentó dificultades para organizar tareas, y el 69.0% se sintió poco valorado por la escuela. Se concluye que se requieren intervenciones integrales y culturalmente adaptadas para fortalecer la salud mental y prevenir el consumo de sustancias en adolescentes.
Keywords: SALUD MENTAL; ESCOLARIDAD; BIOPSICOSOCIAL.; MENTAL HEALTH